OPTIMIZATION OF AN ECONOMIC PRODUCTION QUANTITY-BASED SYSTEM WITH RANDOM SCRAP AND ADJUSTABLE PRODUCTION RATE - Chiu, Yuan-Shyi Peter; Chen, Han-Ying; Chiu, Victoria; Chiu, Singa Wang (Journal of Applied Engineering Science, 2018)
With the aim of increasing capacity to smooth production planning and coping with existence of random scrap in real fabrication processes, this paper explores an economic production quantity (EPQ)-based inventory system with random scrap and adjustable production rate. Mathematical modeling is used to carefully portray and analyze the problem, and the expected system cost function is derived and proved to be a convex function. Then, differential calculus is employed to help determine the optimal batch size for the proposed system. Numerical example along with sensitivity analysis is provided to demonstrate applicability of the obtained results. Analytical outcomes pointed out that this in-depth exploration to the problem reveals diverse important managerial decision-making required information.
Keywords: Economic production quantity; Adjustable production rate; Inventory system; Production planning; Systems; Randomness; Optimizer